Situated ignorance: the distribution and extension of ignorance in cognitive niches - Arfini, Selene (Synthese (Dordrecht), 2021)
Ignorance is easily representable as a cognitive property of more than just individual subjects: groups, crowds, and even populations can share the same ignorance regarding particular concepts and ideas. Nevertheless, according to some theories that refer to the extension, distribution, and situatedness of human cognition, ignorance is hardly a state that can be extended, distributed, and situated in the same way in which knowledge is in our eco-cognitive environment. In order to understand how these contradictory takes can come across in a coherent description of ignorance, in this paper I aim at analyzing the impact of the agent’s ignorance in her ecological and cognitive environment, as well as the effect that the surrounding context has on the agent’s epistemological successes and downfalls. To this end I will adopt the cognitive and empirically sensitive perspectives of the distributed cognition, the extended mind and cognitive niches construction theories, which will help me address and answer three topical questions: (a) adopting the theories about the extended mind, the distributed cognition, and the cognitive significance of affordances can we describe ignorance as extended and distributed in spaces, artifacts, and other people? (b) extending or distributing ignorance in one’s eco-cognitive environment has the same cognitive and ecological impact of extending or distributing knowledge? (c) can we recognize instantiations of externalized or distributed ignorance? I will argue that by acknowledging the extended, distributed, and situated dimension of ignorance in cognitive niches we could recognize the impact that our ignorance and uncertainty has on how we manipulate and organize our environment and also how our eco-cognitive frameworks affect the perception of our epistemological states.